2022
DOI: 10.1262/jrd.2022-001
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin maintains the primordial follicle pool and protects ovarian reserve against cyclophosphamide-induced damage

Abstract: Any abnormal activation of primordial follicles and subsequent depletion can irreversibly diminish the ovarian reserve, which is one of the major chemotherapy-induced adverse effects in young patients with cancer. Herein, we investigated the effects of rapamycin on the activation and development of ovarian follicles to evaluate its fertility-sparing therapeutic value in a cyclophosphamide (CTX)-treated mouse model. Based on ovarian histomorphological changes and follicle counting in 50 SPF female C57BL/6 mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Our data demonstrating the ability of rapamycin to attenuate 4-HC-induced upregulated PI3K signalling in the human ovary is perhaps expected, given the mechanism of action of this well-known inhibitor; this effect has also been reported in multiple rodent studies alongside the chemoprotective efficacy of mTOR inhibitors in general ( Goldman et al , 2017 ; Zhou et al , 2017 ; Tanaka et al , 2018 ; Chen et al , 2022 ). Although not significant in our data, possibly due to limited numbers of growing follicles, other work in rodents has demonstrated the effectiveness of rapamycin treatment in attenuating cyclophosphamide-induced growing follicle damage ( Zhou et al , 2017 ; Chen et al , 2022 ).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our data demonstrating the ability of rapamycin to attenuate 4-HC-induced upregulated PI3K signalling in the human ovary is perhaps expected, given the mechanism of action of this well-known inhibitor; this effect has also been reported in multiple rodent studies alongside the chemoprotective efficacy of mTOR inhibitors in general ( Goldman et al , 2017 ; Zhou et al , 2017 ; Tanaka et al , 2018 ; Chen et al , 2022 ). Although not significant in our data, possibly due to limited numbers of growing follicles, other work in rodents has demonstrated the effectiveness of rapamycin treatment in attenuating cyclophosphamide-induced growing follicle damage ( Zhou et al , 2017 ; Chen et al , 2022 ).…”
Section: Discussionsupporting
confidence: 73%
“…Our data demonstrating the ability of rapamycin to attenuate 4-HC-induced upregulated PI3K signalling in the human ovary is perhaps expected, given the mechanism of action of this well-known inhibitor; this effect has also been reported in multiple rodent studies alongside the chemoprotective efficacy of mTOR inhibitors in general ( Goldman et al , 2017 ; Zhou et al , 2017 ; Tanaka et al , 2018 ; Chen et al , 2022 ). Although not significant in our data, possibly due to limited numbers of growing follicles, other work in rodents has demonstrated the effectiveness of rapamycin treatment in attenuating cyclophosphamide-induced growing follicle damage ( Zhou et al , 2017 ; Chen et al , 2022 ). Although human ovary cortex cultured with rapamycin for 6 days had a high proportion of follicles with fragmented or shrunken oocytes ( McLaughlin et al , 2011 ), this adverse effect on oocyte health was not observed in rodent studies or human ovarian cortical xenotransplantation experiments ( Yorino and Kawamura, 2020 ) nor are there any reports describing adverse reproductive outcomes following rapamycin treatment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This study showed that rapamycin was able to inhibit mTOR pathway activation in ovaries directly after the thawing process and in ovaries five days after grafting in mice [ 61 ]. In addition, Chen et al showed that the injection of rapamycin in mice resulted in lower levels of follicle proliferation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin treatment prevents PFA and preserves the ovarian reserve both in vivo and in vitro in mice ( 203 , 217 222 ) and rats ( 223 ). Rapamycin and everolimus have also been reported to protect the ovarian reserve against chemotherapy-induced early follicular exhaustion in mice by maintaining primordial follicles in a dormant state ( 224 227 ).…”
Section: Primordial Follicle Recruitment Into the Growing Poolmentioning
confidence: 99%